Evaluation of surface sanitation to prevent biological hazards in animal food manufacturing - Muckey, Mary Beth (Kansas State University, 2016)
Animal food manufacturing facilities need to evaluate biological hazards within their facility due to their severity and probability to cause illness or injury in humans or animals. Control of biological hazards, including Salmonella and Porcine Epidemic Diarrhea Virus (PEDV), in animal food manufacturing facilities may require a preventative control to mitigate the risk of the hazard. Thermal processing is an effective point-in-time control, but does not prevent cross-contamination during drying, cooling, and packaging/load-out of animal food. Therefore, it may be appropriate to sanitize surfaces to prevent cross-contamination of animal food during manufacturing. The objective of the first experiment was to evaluate surface decontamination strategies for Porcine Epidemic Diarrhea Virus (PEDV) using chemical disinfectants to reduce viral RNA on various manufacturing surfaces. Concentrated liquid formaldehyde and sodium hypochlorite reduced the quantity of viral PEDV RNA on all tested surfaces. Rubber belting from a bucket elevator retained the most PEDV RNA, while the polyethylene tote bag retained the least. In the second experiment, surface decontamination was evaluated for Salmonella Typhimurium using liquid and dry chemical sanitizers on various manufacturing surfaces. Surfaces treated with concentrated commercial formaldehyde had no detectable Salmonella after treatment, and surfaces treated with medium chain fatty acids (MCFA) had at least a 4-log reduction compared to the control. The dry commercial acidulant, sodium bisulfate, was the most effective dry sanitizer tested, but had limited efficacy depending on surface type. Experiment 3 further tested the application of two chemical sanitizers against Salmonella Enteritidis on residual surface and feed contamination in pilot-scale mixers. Manufacturing sequence, but not treatment impacted feed and surface contamination of Salmonella Enteritidis. Specifically, there was Salmonella-positive residue in the batch of feed manufactured immediately after the positive control batch. However, no Salmonella residue was detected in batches of feed treated with either concentrated commercial essential oil blend or rice hulls treated with 10% MCFA. Low levels of Salmonella residues were observed from feed and surfaces manufactured after Sequence 1, but no residues were observed by Sequence 2. This data suggests that sequencing of feed during manufacturing can reduce Salmonella-positive contamination within animal food and on manufacturing surfaces, particularly after the second batch or with the use of chemical treatments. In summary, liquid sanitizers have been shown to be effective at reducing Salmonella spp. and PEDV contamination on a variety of animal food manufacturing surfaces, but application and practicality may be limited.
Keywords: Feed manufacturing; Surface sanitation; Salmonella; Porcine Epidemic Diarrhea Virus; Biological hazard; Animal food